Urban innovation in the informal city: overlapping infrastructures, co-production and sector coupling in a South African informal settlement - Caprotti, Federico; de Groot, Jiska; Butler, Catherine; Pailman, Whitney; Mathebula, Norman; Schloemann, Hendrik; Densmore, Alex (Frontiers in Sustainable Cities, 2025)
Informal settlements face significant infrastructural challenges, exemplified by limited electricity access in sub-Saharan Africa. We present insights from a 2020–23 research program in a South African informal settlement that highlighted the importance of systems thinking and sector coupling for integrating infrastructural and economic interventions to address the needs of informal settlement populations sustainably. In the program, this was done through solar off-grid electricity innovations and entrepreneurship training. This study’s novelty lies in its expansion of ‘sector coupling’ beyond its conventional technical definition, applying it to socio-technical integration across energy, entrepreneurship, and digital services in an informal urban context. It provides one of the first empirical demonstrations of how systems thinking and co-production can reframe energy provision as a foundation for multidimensional development in the informal city.